Pregnancy outcomes of forced migrants in the Netherlands: A national registry-based study - J.B. Tankink; L.C.M. Bertens; J.P. de Graaf; M.E.T.C. van den Muijsenbergh; J.N. Struijs; B. Goodarzi; A. Franx (Journal of Migration and Health)
Background: The rise of global forced migration urges healthcare systems to respond to the needs of forced migrants (FM) during pregnancy and childbirth. Yet, comprehensive data on the health outcomes of pregnant FM in destination countries remain scarce. This study aimed to describe the characteristics and maternal and perinatal outcomes of pregnancy in this specific migrant population on a national scale in the Netherlands and to explore differences from other populations. Methods: The Dutch perinatal registry was linked to national migration data to analyze pregnancy outcomes in FM (2014–2019), using non-migrants (NM) and resident migrants (RM) as reference populations. We reported outcome rates (% [95 % CI]) for a range of primary and secondary pregnancy outcomes. Primary outcomes included perinatal mortality, small for gestational age infants (SGA), preterm birth, and emergency cesarean section (CS), for which we also calculated the crude relative risk (RR [95 % CI]) of FM compared to NM and RM. In addition, we conducted binary logistic regression analyses on primary outcomes to report adjusted odds ratios (aORs [95 % CIs]) while controlling for multiple births, maternal age and parity. Findings: Compared to the NM group, the FM group had increased risks of perinatal mortality (RR 1.50 [95 % CI 1.20–1.88]), SGA (1.65 [1.59–1.71], and emergency CS (1.19 [1.13–1.25]). Compared to RM, FM still had elevated risks of SGA (1.17 [1.13–1.22]). In contrast, the risk of preterm birth was lower in FM than in NM (0.81 [0.76–0.86]) and RM (0.83 [0.77–0.88]). These differences were confirmed in the adjusted analysis. Differences in secondary outcomes included higher rates of late antenatal care in FM (29.4 % [28.5–30.3]) than in NM (6.7 % [6.6–6.9]) and RM (15.5 % [15.1–15.9]). Rates of planned CS were similarly elevated (14.3 % [95 % CI 13.7–14.8] versus 7.·8 % [7.7–7.8] and 9.6 % [9.5–9.7]), while FM had lower rates of postpartum hemorrhage (3.9 % [3.6–4.2]) versus 6.8 % [6.8–6.9] and 5.7 % [5.6–5.9]). Conclusion: This first Dutch registry-based study demonstrated increased risks of multiple, though not all, adverse pregnancy outcomes in forced migrants. Our results emphasize the imperative to further unravel and address migration-related disparities, dismantle structural barriers to health among forced migrants, and improve the inclusivity of data systems. Collaborative policy, clinical practice, and research efforts are essential to ensure equitable care for every individual, regardless of migration status.